PENERAPAN PRINSIP MATEMATIKA DALAM IURAN SANTRI DI PESANTREN SUBULUSSALAM TULUNGAGUNG JAWA TIMUR - Ni'ami, Nadia Nur Izza; Nafis, Salsabila Khoirun; Setyawan , Bagus Wahyu (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2023)
The purpose of this research is to collect information about the design, preparation, allocation and accountability of education funding at the Subulussalam 2 Tulungagung Islamic Boarding School and regarding information about the factors that influence educational financing at the Subulussalam 2 Tulungagung Islamic Boarding School mathematically. As well as the benefits of education financing management on the quality of education at the Subulussalam 2 Tulungagung Islamic Boarding School. The data was obtained through interviews with one of the pesantren administrators in the finance section or the treasurer. Data analysis in this study is a quantitative method, which in this study is interpreted as part of a series of systematic investigations of phenomena by collecting existing data to then measure with mathematical statistical techniques how to manage education financing at Pondok Subulussalam 2 Tulungagung. The results of this study generally show that education financing management at the Subulussalam 2 Tulungagung Islamic Boarding School Educational Institution has applied the principles of mathematics.